Max Weber’s Social Actions in Chinua Achebe's A Man of the People - Andika Pratama, Moh. Doan (Journal of Literature, Linguistics, & Cultural Studies, 2022)
The purpose of this study was to describe the social action forms of the main characters in the novel A Man of The People according to Max Weber's Social Action Theory. The theory used in this research was Max Weber's social action. The approach used was a sociological approach that focused on literary works because the phenomenon of social action that occured in society was often poured into literary works (Damono, 2004, p. 12). The method of this research was literary criticism. The research data were in the form of excerpts from the contents presented through conversations and narrations as social reality and depictions of social actions carried out by the main characters in the novel. The results obtained from this study were four types of social actions done by the main characters in this novel and how they achieved their own purpose based on their social actions. In the rational-instrumental action, Mr. Nanga did his action 7 times, while Odili only used instrumental actions once. In traditional action, it was found that there were 3 actions related to tradition or actions that were carried out from generation to generation. In the value rational action, it was found that there were 4 actions that were all carried out by Odili. As for the affective action, Odili took 6 actions. This proved that Odili's moral value was higher to achieve his goals. He used more efficient instruments that were counter-humanist such as instrumental rationality just like what Mr. Nanga did. Yet, Odili's goals were not fully fulfilled because his country was overthrown by the Military and his party was dismissed.